Unlocking Learning Group Guidance and Games for Special Needs Students: Membuka Bimbingan Kelompok Belajar dan Permainan untuk Siswa Berkebutuhan Khusus - Rosyidah, Latifatur; Khairi, Alfin Miftahul (Indonesian Journal of Innovation Studies, 2024)
This qualitative study investigates the efficacy of group guidance and games-based learning in enhancing the comprehension of students with special needs at SLB PGRI Plosoklaten. Through observation, interviews, and literature review, the research underscores the crucial role of group guidance in facilitating learning and highlights the effectiveness of integrating games-based learning within this framework. Findings suggest that group guidance aids in material delivery and comprehension, while games-based learning optimizes understanding among students with special needs. The study underscores the significance of these strategies for creating inclusive and effective learning environments, offering valuable insights for educators and policymakers alike. Highlights: Guidance Facilitates Learning: Group guidance aids comprehension for special needs students. Games Enhance Engagement: Games-based learning boosts understanding and participation. Inclusive Education Insights: Findings inform inclusive education practices. Keywords: Games Based Learning, Group Guidance, Special Needs Education